2023
DOI: 10.3390/polym15061566
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymer Electrospinning for Tendon Repairment

Abstract: With the degradation after aging and the destruction of high-intensity exercise, the frequency of tendon injury is also increasing, which will lead to serious pain and disability. Due to the structural specificity of the tendon tissue, the traditional treatment of tendon injury repair has certain limitations. Biodegradable polymer electrospinning technology with good biocompatibility and degradability can effectively repair tendons, and its mechanical properties can be achieved by adjusting the fiber diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 147 publications
0
1
0
Order By: Relevance
“…However, the tendon remodeling stage often takes more than a year, whereas skin tissue heals within a few months. The complications of PA between the tendon and surrounding tissue will further delay repairs of the tendon. Barrier is one of the common ways to prevent PA. Early studies used hyaluronic acid (HA), alginate, and chitosan (CA), separately or in complexes, in the form of hydrogels, films, or fibers, as physical barriers to reduce the PA of the tendon. These studies demonstrated good antiadhesion effects in animal and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tendon remodeling stage often takes more than a year, whereas skin tissue heals within a few months. The complications of PA between the tendon and surrounding tissue will further delay repairs of the tendon. Barrier is one of the common ways to prevent PA. Early studies used hyaluronic acid (HA), alginate, and chitosan (CA), separately or in complexes, in the form of hydrogels, films, or fibers, as physical barriers to reduce the PA of the tendon. These studies demonstrated good antiadhesion effects in animal and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, various materials are widely used in the field of biomedicine. 17–27 Nanofibrous scaffolds made of various materials have shown their potential in nanotechnology. 28 Nanofibers are fibers with a diameter ranging from 1 to 1000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Tendons are strong structures composed of tenocytes, chondrocytes, and synovial cells as well as a predominant extracellular matrix containing type I collagen, elastin, glycoproteins, and proteoglycans [ 1 , 2 ]. These components form fibrils, fibers, and fascicles creating tendons that anchor the muscle to bone [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tendons are strong structures composed of tenocytes, chondrocytes, and synovial cells as well as a predominant extracellular matrix containing type I collagen, elastin, glycoproteins, and proteoglycans [ 1 , 2 ]. These components form fibrils, fibers, and fascicles creating tendons that anchor the muscle to bone [ 1 , 2 ]. Of the possible musculoskeletal injuries, tendon injuries are the most common, with Achilles and patellar tendons being the most common site of injury [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation